DAMPAK DAN MODEL BARU PEMERINTAHAN TERBELAH PASCA PEMILIHAN GUBERNUR KALIMANTAN BARAT TAHUN 2018 - Andi Syarif T. U. W.; Muh. Ilham; Sampara Lukman; Ella Wargadinata (PAPATUNG: Jurnal Ilmu Administrasi Publik, Pemerintahan dan Politik, 2021)
In 2000, the Government of Indonesia took a bold step by adopting a very radical policy of decentralization by devolving broad powers to local governments. The concept of divided government is a new thing that is happening in the government system in Indonesia. This article examines the impact of the governor election in West Kalimantan in 2018 and assesses the current paradigm for divided governance. This study uses a qualitative descriptive method, which provides a complete analysis and analysis of the evidence found. The results show that divided government can have an impact on political and bureaucratic obstacles after the 2018 West Kalimantan Governor Election. The study also found and introduced new methods of implementing split government, namely through ANDI as theoretical implications.